PEMANFAATAN Leuconostoc mesenteroides DAN Lactobacillus plantarum 1 DALAM PEMBUATAN PIKEL PROBIOTIK UMBI BENGKUANG - Dini Elfiani Puteri; Yusmarini; Usman Pato (SAGU, 2022)
The purpose of this research was to determine the appropriate Leuconostoc mesenteroides and Lactobacillus plantarum 1 strains on the microbiological and sensory quality of the probiotic pickles. The research was conducted experimentally by using a completely randomized design with four treatments and four replications. The treatments used in this study were P0 (addition of Leuconostoc mesenteroides), P1 (addition of Leuconostoc mesenteroides + Lactobacillus plantarum 1 RN1-23121), P2 (addition of Leuconostoc mesenteroides + Lactobacillus plantarum 1 RN2-53), P3 (addition of Leuconostoc mesenteroides + Lactobacillus plantarum 1 RN2-12112). The data were analyzed by ANOVA, it was then analyzed by Duncan’s New Multiple Range Test (DNMRT) at α=5% level. The results showed that the addition of Lactobacillus plantarum 1 strains with different amylolytic properties significantly affected acidity (pH), lactid acid, total lactic acid bacteria, as well as descriptive and hedonic sensory assessments of color, aroma, crispness, taste, and overall. The selected treatment was P3 (addition of Leuconostoc mesenteroides + Lactobacillus plantarum 1 RN2-12112) with pH 2.80, lactid acid 0.98%, total lactic acid bacteria 9.57 log CFU/ml with sensory characteristics of yellowish white color, distinctive fermented aroma, crunchy, sour taste, and overall assessment of hedonic was favored by the panelist.